The Profile of Tourist Attractions in Kembang Kuning Tourism Village, East Lombok - Hasnia Minanda; Baiq Nikmatul Ulya; Afan Dwi Mardani (Journal of Finance, Economics and Business, 2023)
The tourism village is a primary focus in the development of the tourism sector in the West Nusa Tenggara (NTB) Province. One of the villages designated as a Tourism Village is Kembang Kuning Village. Kembang Kuning Village has the potential for natural beauty and unique local wisdom. This makes Kembang Kuning Tourism Village one of the most popular Tourism Villages in NTB. However, on the other hand, when viewed from the 4A tourism destination components, some shortcomings are still found. As a guide for developing a tourism village, it is essential to understand its potential and profile first so that, as managers, we are aware of the strengths and distinctive characteristics of the tourism village as a basis that sets it apart from other tourism villages. This makes this research important to be conducted. The general objective of this research is to determine the profile of tourist attractions in Kembang Kuning Tourism Village, East Lombok. Data collection techniques used include observation, interviews, documentation studies, and literature reviews. The data analysis technique used is qualitative descriptive analysis. Based on the explanation of the profile, Kembang Kuning Tourism Village already has the 4A tourism destination components. Supervised by the proactive POKDARWIS Lingkoq Cave and working in partnership with BUMDes, Kembang Kuning Tourism Village is ready for continued development. The combination of cultural diversity, scenic beauty, and effective management positions the village as a potential destination with significant opportunities for future growth in the tourism sector.